Kebijakan PPN atas Jasa Pengelolaan Gedung Diselenggarakan Perhimpunan Penghuni Rumah Susun Strata Title: Studi Kasus pada Apartemen LR - Dewi, Maya Safira; Aryani, Winda (Binus Business Review, 2011)
Building management service that delivered by appartment tenant association is categorized as service that not imposed PPN. Subject determination PPN becoming not clear, because definition difference between this hand bill and the rules of hits honor bound party collects PPN. Though apartment tenant association LR have circulation bruto exceeds definition small entrepreneur, tenant association remain not to be obliged as taxable employers. Evaluated from PPN object also not gives rule of law because intrinsically its service included in facility understanding or amenity or rights is available to weared as understanding taxable service as the same manner as determined by section 4 UU PPN, until provisions in this handbill opposes against rule on it. Evaluated from elementary imposition PPN generates indistinctness the level of income that obtained from management fee can become elementary imposition PPN or not, because existed difference of object definition PPN between hand bill and the rules of other PPN.